The The Exploitation of Laura Edelenyi's Departure: A Study of Social Semiotics in the Deddy Corbuzier Podcast - Tesalonika Hasugian; Patricia Robin (PUBLIC CORNER, 2022)
The diversity of media trends appears on podcast channels channeled through YouTube. Podcasts have been considered a development form of digital radio. One of the famous YouTubers in Indonesia is Deddy Corbuzier, the owner of the YouTube channel "Corbuzier Podcast: Close The Door". Her video podcast titled “GOODBYE LAURA... NETIZEN, DENGAR SAYA KALI INI !!” caught the audience’s attention when creating and uploading the video with all the emotional attributes. The research discussion uses the study of social semiotics goals to describe the signs of the semiotic resources presented and the interaction of images with the audience. This research method will focus on the qualitative description. The data collection used a literature study. The Research Team saw that the content presented contained an element of exploitation for the departure of Laura Edelenyi was immediately deliberately displayed by Deddy Corbuzier, a sign owner with a specific motivation behind it. The results showed Deddy and Laura's personal relationship had created a deep meaning of loss. However, the insertion of advertising in no way corresponds to the signs symbolized by the communicator.